Biogeochemical sulfide mineralization in the volcanic-hosted Tongguan hydrothermal field, southern Mid-Atlantic Ridge - Li, Bing; Shi, Xuefa; Li, Chuanshun; Wang, Sai; Ye, Jun; Yan, Quanshu; Dang, Yuan; Fang, Xisheng (Frontiers in Marine Science, 2025)
Biogeochemical mineralization is increasingly recognized as a significant factor in the formation of submarine hydrothermal sulfide deposits. While several mechanisms by which hydrothermal organisms may facilitate metal deposition have been documented in many seafloor hydrothermal deposits, the potential involvement of biogenic processes in the mineralization of hydrothermal deposits in the southern Mid-Atlantic Ridge (SMAR) has been largely overlooked until now. In this study, we investigate sulfide chimney sample from the volcanic-hosted Tongguan hydrothermal field on the SMAR and present several lines of evidence for biogeochemical mineralization. Mineralogical analysis infers four types of biogenic pyrite and chalcopyrite structures: macrobiotic-related tube structures, microbial-related quasi-stromatolite, quasi-oncolite and globular structures. These biogenic structures exhibit selective enrichment of elements such as Mn, Pb, and Cu in biogenic pyrite compared to abiotic pyrite. In-situ sulfur isotope studies indicate that biogenic minerals possess lower δ34S values than abiotic minerals. We identified three biomineralization mechanisms: an “active” mineralization process mediated by macro-organism, a “passive” mineralization process associated with microbial mats, and a microbial assimilatory sulfate reduction process. Our research suggests that the role of biogenic processes in SMAR hydrothermal mineralization should be given further consideration.